2015
DOI: 10.1038/onc.2015.201
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: MiR-873 regulates ERα transcriptional activity and tamoxifen resistance via targeting CDK3 in breast cancer cells

et al.

Abstract: , requested the authors who have listed the University in their affiliation to remove the affiliation from this publication as the study was not performed at the University and was not associated with their roles at the University. As a result, the authors have requested Mingjun Bi, Anne-Marie Overstreet and Alex Meredith be removed from the author list and listed instead under the Acknowledgement section of the paper. Xingyuan Yang had already left the University of Cincinnati and carried out some work at his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…40 Indeed, upregulation of aromatase expression is found in tamoxifen-resistant human breast cancer. 23 Moreover, our results also indicated that forced CREB1 expression increased aromatase expression. Notably, recent evidence suggests that miR-27b-3p enhances cytotoxicity of drugs by targeting inhibition of ENPP1, which induces ABCG2 expression and cell surface localization and increases drugs efflux.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…40 Indeed, upregulation of aromatase expression is found in tamoxifen-resistant human breast cancer. 23 Moreover, our results also indicated that forced CREB1 expression increased aromatase expression. Notably, recent evidence suggests that miR-27b-3p enhances cytotoxicity of drugs by targeting inhibition of ENPP1, which induces ABCG2 expression and cell surface localization and increases drugs efflux.…”
Section: Discussionsupporting
confidence: 60%
“…22, 23, 24 Downregulation of miR-375 and miR-873 are associated with tamoxifen resistance, whereas overexpression of miR-375 and miR-873 increases tamoxifen sensitivity in breast cancer. 22, 23 In this study, we identified miR-27b-3p exhibited decreased expression in tamoxifen-resistant breast cancer tissues and cells. In addition, we had shown for the first time the role of miR-27b-3p in conferring sensitivity of breast cancer to tamoxifen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…miR-323 was shown to upregulate VEGF-A and increase vascularization in prostate cancer [30]. In a recent study, miR-873 was shown to be downregulated in breast tumors and to play a tumor suppressor role by targeting cyclin-dependent kinase 3, leading to the inhibition of ER-α activity and the suppression of breast cancer cell proliferation and tumor growth [31]. Insulin-like growth factor 2 mRNA binding protein 1 (IGFBP1) was identified as a target of miR-873 in glioblastoma [32].…”
Section: Discussionmentioning
confidence: 99%
“… 20 , 21 , 22 Cui et al. 23 have shown that miR-873-5p attenuates tamoxifen resistance by targeting CDK3 and modulates ERα transcriptional activity in breast cancer cells. We recently indicate that miR-873-5p suppresses the stemness of breast cancer cells through targeting PD-L1, an immune checkpoint, and thus suppressing the PI3K/AKT and ERK1/2 signaling pathways.…”
Section: Introductionmentioning
confidence: 99%